The Role of Women Translators in the Galician Literary Field - Luna Alonso, Ana (Madrygal. Revista de Estudios Gallegos, 2017)
The main objective of this article is to highlight the role played by women responsible for literary translations done into Galician after the democratic period, as well as to establish a proposal to classify their professional profiles within the framework of the publishing sector. This research on the functions carried out by women translators and their social development as intercultural mediators, transfer agents, project initiators and repertoire producers with capacity to introduce new debates on publishing policy of the works published, was carried out by analysing texts from the BITRAGA database. This paper throws light on whether the route taken responds to an order or the personal choice of the woman translator who tries to give visibility to a certain work or author. The case study performed and the works analysed are representative and significant to the Galician literary field.
Keywords: Translation Studies; Literary Field; Translated Literary Works; Women Translators; Classification.